A composite hollow fiber ceramic membrane and preparation method thereof
Through the combination of phase conversion wet and dry spinning technology and nanoadditives, the toughness and hydrophilicity of the ceramic membrane are improved, and the problems of insufficient brittleness and hydrophilicity of the ceramic membrane are solved, and the separation efficiency and permeability are achieved. It is suitable for Industrial water treatment.
Patent Information
- Application Number
- CN202310011615.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-05
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-01-05
AI Technical Summary
The existing ceramic membrane materials have low brittleness and insufficient hydrophilicity, resulting in low separation efficiency and permeability, making them difficult to widely use in industrial applications.
Using phase conversion wet and dry spinning technology, N-methylpyrrolidone or polyethylene glycol aqueous solution is used as the solidification bath, and yttrium oxide stabilized zirconia, zirconia and alumina are added as ceramic powders, combining silicon carbide and dioxide Silicon or molecular sieve is used as nanoadditives to improve the toughness and hydrophilicity of the membrane by adjusting the ratio of ceramic powder and nanoadditives.
It significantly improves the toughness and hydrophilicity of ceramic membranes, improves separation efficiency and permeability, reduces membrane pollution, and is suitable for industrial water treatment.
Smart Images

Figure BDA0004038968500000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of membrane material preparation, and in particular relates to a composite hollow fiber ceramic membrane and a preparation method thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Membrane separation technology is an efficient, energy-saving and environmentally friendly separation technology. It has been widely used in the fields of liquid and gas separation, sewage treatment, drinking water industry and seawater desalination. According to the appearance and structure of ceramic membranes, they can be divided into flat membranes, single-channel tubular membranes, multi-channel tubular membranes and hollow fiber membranes. Among them, flat membranes are not conducive to large-scale industrial applications due to their low assembly density and are mainly used for small-scale industrial applications and laboratory research. The packing density and membrane strength of single-channel tubular membranes are also low, so the low separation efficiency makes it unfavorable for industrial application; although the mechanical strength and assembly density of multi-channel tubular membranes have been improved, their production cost is too high; and hollow fiber ceramic membranes have a large assembly density and a simple and convenient preparation process. At the same time, due to the asymmetric structure of the hollow fiber membrane, it has a high permeability and separation efficiency, which makes the hollow fiber ceramic membrane widely concerned by more researchers.
[0004] Due to the inherent brittleness of ceramic materials, they are very likely to suffer brittle fracture due to stress concentration caused by defects on the surface or inside. Therefore, the strengthening and toughening of porous ceramic membranes has become an urgent problem that needs to be solved. At the same time, how to further improve the hydrophilicity of hollow fiber ceramic membranes so that they can obtain higher permeability and lower membrane fouling in the water treatment process is also a problem that needs to be solved urgently. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a composite hollow fiber ceramic membrane and a preparation method thereof, which can effectively improve the toughness and hydrophilicity of the membrane.
[0006] The preparation method of the composite hollow fiber ceramic membrane in the present invention is a phase inversion dry-wet spinning technology, using an aqueous solution containing N-methylpyrrolidone or polyethylene glycol as a coagulation bath. Studies have shown that adding a solvent to the coagulation bath will reduce the polymer concentration at the film interface, while reducing the non-solvent activity and the diffusion rate into the polymer membrane, thereby further delaying stratification, which will result in the membrane having a smoother surface and a smaller surface roughness. At the same time, the porous sponge layer produced can effectively reduce the passage resistance of the permeate and increase the water flux of the membrane.
[0007] Using yttria-stabilized zirconia, zirconium oxide and alumina as ceramic powders, and silicon carbide, silicon dioxide, molecular sieve or polyethylene glycol-coated upconversion nanoparticles as nanoadditives, studies have shown that in order to increase the wall strength between the voids in porous ceramics, reinforcing materials need to be added. The most effective additives are carbides and oxides in the form of particles, fibers or tubes. At the same time, in order to avoid the size of the particles affecting the membrane pore structure, nano-sized additives should be used; at the same time, when two sizes of ceramic powders and nanoadditives are mixed, the smaller particles will fill the unoccupied gaps between the large particles. Therefore, as long as the ratio of nanoadditives is appropriate, the ratio of ceramic powders can reach the stage of mutual contact to obtain the best filling density, thereby improving the toughness of the ceramic membrane. At the same time, due to the inherent hydrophilicity of the nanoadditives themselves, the hydrophilicity of the ceramic membrane can also be improved, thereby obtaining higher separation efficiency and better permeability. Citric acid is used as a nanodispersant to inhibit the agglomeration of nanoadditives.
[0008] In order to achieve the above object, the present invention adopts the following technical solutions:
[0009] A method for preparing a composite hollow fiber ceramic membrane comprises the following steps:
[0010] (1) adding an additive to an organic solvent and stirring the mixture to obtain a casting solution A; sequentially adding a ceramic powder, a nanoparticle dispersant and a nanoadditive to the casting solution A and stirring the mixture in a ball mill to obtain a casting solution B; adding a polymer binder to the casting solution B and stirring the mixture to obtain a uniformly dispersed casting solution C;
[0011] (2) degassing the casting liquid C under vacuum; extruding the casting liquid C from the tube hole spinneret into an external coagulation bath through a syringe pump to complete the phase inversion process, thereby obtaining a hollow fiber ceramic membrane precursor;
[0012] (3) Sintering the composite hollow fiber ceramic membrane: After the hollow fiber ceramic membrane precursor is dried at room temperature, it is sintered in a tubular furnace in two steps at high temperature to finally obtain the composite hollow fiber ceramic membrane.
[0013] Furthermore, the ceramic powder is Al 2 O 3 、ZrO 2 , one or more of yttria-stabilized zirconium oxide powders, the powder particle size is 0.3 to 5 microns, and the addition amount is 30% to 60% of the total mass of the casting liquid C.
[0014] Furthermore, the nano-dispersant is citric acid, and its addition amount is 0-1% of the total mass of the casting solution C.
[0015] Furthermore, the nano-additive is silicon carbide, silicon dioxide, molecular sieve or polyethylene glycol coated upconversion nanoparticles, and the amount of nano-particles added is not included in the total amount of the casting solution. The amount added is the mass fraction of the ceramic powder in the ceramic powder and nano-particle additive sample, which is 0-50%.
[0016] Furthermore, the polymer binder is one or more of polyethersulfone, polysulfone and polyetherimide, and the addition amount thereof is 5-25% of the total mass of the casting solution C.
[0017] Furthermore, the organic solvent is one or more of N-methylpyrrolidone, dimethylformamide, dimethylacetamide and dimethyl sulfoxide, and the added amount thereof is 35-55% of the total mass of the casting solution C.
[0018] Furthermore, the additive is polyvinyl pyrrolidone, solsperse 3000, polyethylene glycol-30 dipolyhydroxystearate, propionic acid, sorbitan oleate, polyethylene oxide or O-(2-aminopropyl)-O · -(2-methoxyethyl)-polypropylene glycol, the addition amount of which is 1% to 8% of the total mass of the casting solution C.
[0019] Furthermore, before adding, the ceramic powder and nanoparticle additives are fully dried at 70°C to ensure that no moisture is retained.
[0020] Furthermore, after the casting liquid A is fully ground in a planetary ball mill, a polymer binder is added and the grinding is continued until the system is uniformly dispersed, and finally it is degassed under vacuum to remove excessive bubbles trapped therein, and finally the casting liquid is obtained.
[0021] Furthermore, in the preparation of the hollow fiber ceramic membrane precursor in step (2), water or anhydrous ethanol is used as the core liquid, water, an aqueous solution containing 1-5% N-methylpyrrolidone or an aqueous solution containing 1-5% polyethylene glycol is used as the coagulation bath, the extrusion pressure is 0.03-0.2MPa, and the casting liquid C enters the coagulation bath after passing through an air gap of 2-20 cm and undergoes phase transformation in the coagulation bath for 24 hours.
[0022] Furthermore, in the high temperature sintering process of the hollow fiber ceramic membrane precursor in step (3), the temperature is first increased to 400-600°C at a heating rate of 2-6°C / min to remove organic components in the hollow fiber ceramic membrane precursor, and then increased to 1000-1600°C at a heating rate of 2-6°C / min and maintained for 8-12 hours, and finally gradually cooled to room temperature at a cooling rate of 3-5°C / min to finally obtain a composite hollow fiber ceramic membrane.
[0023] The advantages of the present invention are:
[0024] By optimizing the raw materials and preparation process, blending ceramic raw materials with different particle sizes and loading nano-additives, and adjusting the ratio to achieve the optimal filling density, the toughness of the ceramic membrane can be improved, and the toughness and compressive strength of the composite ceramic membrane made from the casting liquid can be further improved. At the same time, due to the addition of inherently hydrophilic nano-additives, the hydrophilic properties of the ceramic membrane can be improved; at the same time, an aqueous solution containing N-methylpyrrolidone or an aqueous solution containing polyethylene glycol is used as a coagulation bath, so that the water flux of the final ceramic membrane is further improved. DETAILED DESCRIPTION
[0025] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0026] Example 1
[0027] A method for preparing a composite hollow fiber ceramic membrane comprises the following process steps:
[0028] Step 1: Prepare the casting solution
[0029] 1.1 Place the ceramic powder in a 70℃ oven and fully dry it to ensure that there is no moisture retention;
[0030] 1.2 Add polyethylene glycol-30 dipolyhydroxystearate to N-methylpyrrolidone, wherein the addition amount of polyethylene glycol-30 dipolyhydroxystearate is 5%, and the addition amount of N-methylpyrrolidone is 35%, and the casting solution A is obtained by sufficient stirring;
[0031] 1.3 Add yttria-stabilized zirconia to the casting solution A and stir it in a ball mill to obtain a casting solution B to ensure that the ceramic particles, solvent and additives are fully mixed, wherein the addition amount of yttria-stabilized zirconia is 40%;
[0032] 1.4 Add polyethersulfone to the casting solution B and stir thoroughly to form a uniformly dispersed casting solution C, wherein the addition amount of polyethersulfone is 20%.
[0033] 1.5 Degas the casting solution C under vacuum;
[0034] Step 2: Preparation of hollow fiber ceramic membrane precursor
[0035] 2.1 The casting liquid C is extruded through a tubular orifice spinneret with a nitrogen pressure of 0.1 MPa, and the internal coagulant (core liquid) is pumped into the spinneret hole. Then, after passing through an air gap of 10 cm, the green hollow fiber body is immersed in an external coagulation bath for 24 hours to complete the phase transformation process. The precursor is then dried in air at room temperature (25°C) to finally obtain a hollow fiber ceramic membrane precursor; wherein the internal coagulation bath: water, the internal coagulation bath flow rate: 20 mL / min; the external coagulation bath: water; the extrusion speed: 22 mL / min; the spinning head size: 1.3 mm / 2.5 mm.
[0036] Step 3: Sintering the composite hollow fiber ceramic membrane
[0037] 3.1 After the precursor is dried at room temperature, the temperature is increased to 500°C at a heating rate of 2°C / min and kept for 2 hours to remove the organic components in the hollow fiber ceramic membrane precursor, and then the temperature is increased to 1500°C at a heating rate of 5°C / min and kept for 12 hours, and finally the temperature is gradually cooled to room temperature at a cooling rate of 5°C / min to finally obtain a porous high-strength hollow fiber ceramic membrane.
[0038] Example 2
[0039] A method for preparing a composite hollow fiber ceramic membrane comprises the following process steps:
[0040] Step 1: Prepare the casting solution
[0041] 1.1 Place the ceramic powder in a 70℃ oven and fully dry it to ensure that there is no moisture retention;
[0042] 1.2 Add polyethylene glycol-30 dipolyhydroxystearate to N-methylpyrrolidone, wherein the addition amount of polyethylene glycol-30 dipolyhydroxystearate is 5%, and the addition amount of N-methylpyrrolidone is 35%, and the casting solution A is obtained by sufficient stirring;
[0043] 1.3 Add yttria-stabilized zirconia to the casting solution A and stir it in a ball mill to obtain a casting solution B to ensure that the ceramic particles, solvent and additives are fully mixed, wherein the addition amount of yttria-stabilized zirconia is 40%;
[0044] 1.4 Add polyethersulfone to the casting solution B and stir thoroughly to form a uniformly dispersed casting solution C, wherein the addition amount of polyethersulfone is 20%.
[0045] 1.5 Degas the casting solution C under vacuum;
[0046] Step 2: Preparation of hollow fiber ceramic membrane precursor
[0047] 2.1 The casting liquid C is extruded through a tubular spinneret with a nitrogen pressure of 0.1 MPa, and the internal coagulant (core liquid) is pumped into the spinneret hole. Then, after passing through an air gap of 10 cm, the green hollow fiber body is immersed in an external coagulation bath for 24 hours to complete the phase transformation process, and then the precursor is dried in air at room temperature (25°C) to finally obtain a hollow fiber ceramic membrane precursor; wherein the internal coagulation bath: water, the internal coagulation bath flow rate: 20 mL / min; the external coagulation bath: an aqueous solution containing 4% N-methylpyrrolidone; the extrusion speed: 22 mL / min; the spinning head size: 1.3 mm / 2.5 mm.
[0048] Step 3: Sintering the composite hollow fiber ceramic membrane
[0049] 3.1 After the precursor is dried at room temperature, the temperature is increased to 500°C at a heating rate of 2°C / min and kept for 2 hours to remove the organic components in the hollow fiber ceramic membrane precursor, and then the temperature is increased to 1500°C at a heating rate of 5°C / min and kept for 12 hours, and finally the temperature is gradually cooled to room temperature at a cooling rate of 5°C / min to finally obtain a porous high-strength hollow fiber ceramic membrane.
[0050] Example 3
[0051] A method for preparing a composite hollow fiber ceramic membrane comprises the following process steps:
[0052] Step 1: Prepare the casting solution
[0053] 1.1 Place the ceramic powder in a 70℃ oven and fully dry it to ensure that there is no moisture retention;
[0054] 1.2 Add polyethylene glycol-30 dipolyhydroxystearate to N-methylpyrrolidone, wherein the addition amount of polyethylene glycol-30 dipolyhydroxystearate is 5%, and the addition amount of N-methylpyrrolidone is 35%, and the casting solution A is obtained by sufficient stirring;
[0055] 1.3 Add yttria-stabilized zirconia to the casting solution A and stir it in a ball mill to obtain a casting solution B to ensure that the ceramic particles, solvent and additives are fully mixed, wherein the addition amount of yttria-stabilized zirconia is 40%;
[0056] 1.4 Add polyethersulfone to the casting solution B and stir thoroughly to form a uniformly dispersed casting solution C, wherein the addition amount of polyethersulfone is 20%.
[0057] 1.5 Degas the casting solution C under vacuum;
[0058] Step 2: Preparation of hollow fiber ceramic membrane precursor
[0059] 2.1 The casting liquid C is extruded through a tubular orifice spinneret with a nitrogen pressure of 0.1 MPa, and the internal coagulant (core liquid) is pumped into the spinneret hole. Then, after passing through an air gap of 10 cm, the green hollow fiber body is immersed in an external coagulation bath for 24 hours to complete the phase transformation process, and then the precursor is dried in air at room temperature (25°C) to finally obtain a hollow fiber ceramic membrane precursor; wherein the internal coagulation bath: water, the internal coagulation bath flow rate: 20 mL / min; the external coagulation bath: an aqueous solution containing 4% polyethylene glycol; the extrusion speed: 22 mL / min; the spinning head size: 1.3 mm / 2.5 mm.
[0060] Step 3: Sintering the composite hollow fiber ceramic membrane
[0061] 3.1 After the precursor is dried at room temperature, the temperature is increased to 500°C at a heating rate of 2°C / min and kept for 2 hours to remove the organic components in the hollow fiber ceramic membrane precursor, and then the temperature is increased to 1500°C at a heating rate of 5°C / min and kept for 12 hours, and finally the temperature is gradually cooled to room temperature at a cooling rate of 5°C / min to finally obtain a porous high-strength hollow fiber ceramic membrane.
[0062] Example 4
[0063] A method for preparing a composite hollow fiber ceramic membrane comprises the following process steps:
[0064] Step 1: Prepare the casting solution
[0065] 1.1 Place the ceramic powder and nanoparticle additives in a 70°C oven and fully dry them to ensure that no moisture is retained;
[0066] 1.2 Add polyethylene glycol-30 dipolyhydroxystearate to N-methylpyrrolidone, wherein the addition amount of polyethylene glycol-30 dipolyhydroxystearate is 5%, and the addition amount of N-methylpyrrolidone is 35%, and the casting solution A is obtained by sufficient stirring;
[0067] 1.3 Add yttria-stabilized zirconium oxide, silicon carbide and citric acid to the casting solution A and stir the solution in a ball mill to obtain a casting solution B, so as to ensure that the ceramic particles, the solvent and the additives are fully mixed, wherein the addition amount of yttria-stabilized zirconium oxide is 40%, the addition amount of citric acid is 0.6%, and the loading amount of silicon carbide is 5%;
[0068] 1.4 Add polyethersulfone to the casting solution B and stir thoroughly to form a uniformly dispersed casting solution C, wherein the added amount of polyethersulfone is 19.4%.
[0069] 1.5 Degas the casting solution C under vacuum;
[0070] Step 2: Preparation of hollow fiber ceramic membrane precursor
[0071] 2.1 The casting liquid C is extruded through a tubular spinneret with a nitrogen pressure of 0.1 MPa, and the internal coagulant (core liquid) is pumped into the spinneret hole. Then, after passing through an air gap of 10 cm, the green hollow fiber body is immersed in an external coagulation bath for 24 hours to complete the phase transformation process, and then the precursor is dried in air at room temperature (25°C) to finally obtain a hollow fiber ceramic membrane precursor; wherein the internal coagulation bath: water, the internal coagulation bath flow rate: 20 mL / min; the external coagulation bath: an aqueous solution containing 4% N-methylpyrrolidone; the extrusion speed: 22 mL / min; the spinning head size: 1.3 mm / 2.5 mm.
[0072] Step 3: Sintering the composite hollow fiber ceramic membrane
[0073] 3.1 After the precursor is dried at room temperature, the temperature is increased to 500°C at a heating rate of 2°C / min and kept for 2 hours to remove the organic components in the hollow fiber ceramic membrane precursor, and then the temperature is increased to 1500°C at a heating rate of 5°C / min and kept for 12 hours, and finally the temperature is gradually cooled to room temperature at a cooling rate of 5°C / min to finally obtain a porous high-strength hollow fiber ceramic membrane.
[0074] Example 5
[0075] The difference from Example 4 is that the loading amount of silicon carbide is 15%.
[0076] Example 6
[0077] The difference from Example 4 is that the loading amount of silicon carbide is 25%.
[0078] Example 7
[0079] The difference from Example 5 is: Nanoparticle additive: silicon dioxide.
[0080] Example 8
[0081] The difference from Example 5 is: Nanoparticle additive: polyethylene glycol-coated upconversion nanoparticles.
[0082] Example 9
[0083] The difference from Example 5 is: nanoparticle additive: HZSM-5; calcination temperature: 1000°C.
[0084] Example 10
[0085] The difference from Example 2 is that the coagulation bath is an aqueous solution containing 2% N-methylpyrrolidone.
[0086] Embodiment 11
[0087] The difference from Example 2 is that the coagulation bath is an aqueous solution containing 5% N-methylpyrrolidone.
[0088] Example 12
[0089] The difference from Example 3 is that the coagulation bath is an aqueous solution containing 2% polyethylene glycol.
[0090] Example 13
[0091] The difference from Example 3 is that the coagulation bath is an aqueous solution containing 2% polyethylene glycol.
[0092] Performance testing
[0093] The composite hollow fiber ceramic membranes prepared in Examples 1-13 were used to perform performance tests. The test results are shown in Table 1:
[0094] Table 1
[0095]
[0096] In combination with Examples 1, 2 and 3, it can be seen that the composition of different coagulation liquids in the membrane-forming slurry will have a huge impact on the performance of the hollow fiber ceramic membrane finally formed. The coagulation liquid composition used in the membrane-forming slurry in Example 2 is the best, and the hollow fiber ceramic membrane obtained has the largest porosity, the highest pure water flux, the best hydrophilicity, and the best compressive strength.
[0097] In combination with Example 1, Example 2 and Example 4, it can be seen that in Example 4, silicon carbide and citric acid are added to the casting liquid, wherein the amount of citric acid added is 0.6%, and the loading amount of silicon carbide is 5%; when the coagulation bath is an aqueous solution containing 4% N-methylpyrrolidone, the compressive strength and hydrophilicity of the prepared hollow fiber ceramic membrane are greatly improved while ensuring good porosity and water flux.
[0098] In combination with Example 4, Example 5 and Example 6, it can be seen that the loading amounts of the nanoparticle additive silicon carbide added to the casting solution are 5%, 15% and 25%. Among them, when the loading amount of silicon carbide is 15%, the compressive strength and hydrophilicity of the prepared hollow fiber ceramic membrane are maximized while ensuring good porosity and water flux.
[0099] In combination with Example 5, Example 7, Example 8 and Example 9, it can be seen that the nanoparticle additives added to the casting solution are silicon carbide, silicon dioxide, polyethylene glycol-coated upconversion nanoparticles and HZSM-5 (calcination temperature: 1000°C), respectively. Among them, when the added nanoparticle additive is silicon carbide, the compressive strength and hydrophilicity of the prepared hollow fiber ceramic membrane are maximized.
[0100] In combination with Example 2, Example 10 and Example 11, it can be seen that the concentrations of N-methylpyrrolidone in the external coagulation bath added to the casting liquid are 2%, 4% and 5%, respectively. Among them, when the concentration of N-methylpyrrolidone in the external coagulation bath is 4%, the porosity, water flux and compressive strength of the prepared hollow fiber ceramic membrane are maximized.
[0101] In combination with Example 3, Example 13 and Example 14, it can be seen that the concentrations of polyethylene glycol in the external coagulation bath added to the casting liquid are 2%, 4% and 5%, respectively. Among them, when the concentration of polyethylene glycol in the external coagulation bath is 4%, the porosity, water flux and compressive strength of the prepared hollow fiber ceramic membrane are maximized.
[0102] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to perform equivalent replacements on parts thereof. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention. Although the above describes the specific implementation methods of the present invention, it is not intended to limit the protection scope of the present invention. Those skilled in the art should understand that, based on the technical solution of the present invention, various modifications or deformations that can be made by those skilled in the art without creative labor are still within the protection scope of the present invention.
Claims
1. A method for preparing a composite hollow fiber ceramic membrane, characterized in that: The following steps are involved: (1) Adding additives to an organic solvent and stirring them thoroughly to obtain a casting liquid A; adding ceramic powder, a nanoparticle dispersant and a nanoadditive to the casting liquid A in sequence and stirring them thoroughly in a ball mill to obtain a casting liquid B; adding a polymer binder to the casting liquid B and stirring them thoroughly to form a uniformly dispersed casting liquid C; (2) degassing the casting liquid C under vacuum; extruding the casting liquid C from the tube hole spinneret into an external coagulation bath through a syringe pump to complete the phase inversion process, thereby obtaining a hollow fiber ceramic membrane precursor; (3) Sintering the composite hollow fiber ceramic membrane: After the hollow fiber ceramic membrane precursor is dried at room temperature, it is sintered in a tubular furnace in two steps at high temperature to finally obtain the composite hollow fiber ceramic membrane; The nano additive is silicon carbide, silicon dioxide, molecular sieve or polyethylene glycol coated upconversion nanoparticles, and its loading amount is 0-50% of the amount of ceramic powder added; The organic solvent is one or more of N-methylpyrrolidone, dimethylformamide, dimethylacetamide and dimethyl sulfoxide, and the added amount is 35-55% of the total mass of the casting solution C; The ceramic powder is one or more of ZrO2 and yttria-stabilized zirconium oxide powders, the particle size of the powder is 0.3-5 microns, and the addition amount thereof is 30%-60% of the total mass of the casting liquid C.
2. The preparation method according to claim 1, characterized in that: The additive is polyvinyl pyrrolidone, solsperse3000, polyethylene glycol-30 dipolyhydroxystearate, propionic acid, sorbitan oleate, polyethylene oxide or O-(2-aminopropyl)-O · -(2-methoxyethyl)-polypropylene glycol, the addition amount of which is 1% to 8% of the total mass of the casting solution C.
3. The preparation method according to claim 1, characterized in that: The nano-dispersant is citric acid, and its addition amount is 0-1% of the total mass of the casting solution C.
4. The preparation method according to claim 1, characterized in that: The polymer binder is one or more of polyethersulfone, polysulfone and polyetherimide, and the added amount thereof is 5-25% of the total mass of the casting solution C.
5. The preparation method according to claim 1, characterized in that: Before adding, the ceramic powder and nanoparticle additives were fully dried at 70°C to ensure that no moisture was retained.
6. The preparation method according to claim 1, characterized in that: After the casting liquid A is fully ground in a planetary ball mill, a polymer binder is added and grinding is continued until the system is uniformly dispersed. Finally, it is degassed under vacuum to remove excessive bubbles trapped therein, and finally a casting liquid is obtained.
7. The preparation method according to claim 1, characterized in that: In the preparation of the hollow fiber ceramic membrane precursor in step (2), water or anhydrous ethanol is used as the core liquid, water, an aqueous solution containing 1-5% N-methylpyrrolidone or an aqueous solution containing 1-5% polyethylene glycol is used as the coagulation bath, the extrusion pressure is 0.03-0.2 MPa, the casting liquid C enters the coagulation bath after passing through an air gap of 2-20 cm, and phase conversion is carried out in the coagulation bath for 24 hours; Alternatively, the high temperature sintering process of the hollow fiber ceramic membrane precursor in the step (3) is first heated to 400-600°C at a heating rate of 2-6°C / min to remove organic components in the hollow fiber ceramic membrane precursor, then heated to 1000-1600°C at a heating rate of 2-6°C / min and maintained for 8-12 hours, and finally cooled to room temperature at a cooling rate of 3-5°C / min to finally obtain a composite hollow fiber ceramic membrane.
8. The composite hollow fiber ceramic membrane prepared according to the preparation method according to any one of claims 1 to 7.